Communicating good territorial practices in the European Union - Angulo Egea, María; Hernández Navarro, María Luz (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article presents the results of an innovation project based on an interdisciplinary work between students of two degrees taught at the University of Zaragoza: the Degree in Geography and Spatial Planning (Territorial Policies and Strategies of the European Union) and the Degree in Journalism (Specialized Communication Projects). This collaborative practice applies the project-based methodology to analyze and disseminate good territorial practices in the EU related to the Sustainable Development Goals 2030. It involves reinforcing teamwork skills, sharing the experience of practicing professionals and testing professional practiceAbstract in English.